Effectiveness of a project-based learning digital booklet developed with the 4D model - Mukra, Rizal; Rahima, Tazkia Khansa Putri; Satipa, Oriza; Syahra, Assyfa; Tarigan, Adelia Br.; Hijriyanti, Putri (STKIP Persada Khatulistiwa Sintang, 2025)
The role of education is very important in producing quality human resources, one of which is through improving the quality of biology learning in schools. This study aims to determine the effectiveness of digital booklet-based PjBL (Project-Based Learning) learning media on the developed motion system material. The low level of conceptual understanding among 11th-grade students at SMAN 2 Binjai is caused by conventional learning methods and the lack of interactive media. The research method applied is a development study (R&D) using the 4D model (Define, Design, Develop, and Disseminate). The effectiveness of the media is measured by comparing pretest and posttest results, which are then analyzed using the N-Gain formula. The research findings indicate that this digital booklet is quite effective in improving learning outcomes, conceptual understanding, and student mobility. The average N-Gain score was 0.73, which falls into the moderate category. Therefore, it is concluded that the developed booklet is effective in its use as an innovative learning solution in the classroom.